Comparison of coarsening behaviour in non-conserved and volume-conserved isotropic two-phase grain structures. (15th March 2018) - Yadav, Vishal; Moelans, Nele
Abstract: Microstructure evolution in non-conserved and volume-conserved isotropic two-phase grain structures, with equal interfacial energy for all interfaces and equal volume fractions of the two-phases, is compared based on large-scale phase-field simulations. Two important observations are as follows: (1) the growth mechanism has a larger effect on the grain size distributions of the two alloys than on their grain topology distributions; (2) the growth rate and normalized grain size relation of the grains per topological class are much more scattered for the conserved system than the non-conserved system. Graphical Abstract: